Influence of 4A’s Tourism Component, Memorable Tourist Experiences and Revisit Intention at Taman Sari Yogyakarta - Susanti, Dewi Noor (Institute of Computer Science (IOCS), 2025)
Tourism with historical and cultural nuances currently has its own appeal for tourists. Taman Sari Yogyakarta offers a combination of cultural and historical tourism that can create a unique impression for tourists and impact their intention to revisit. However, there is still a research gap regarding the influence of tourism components on revisit intention. Therefore, the purpose of this study is to examine the influence of the 4A tourism components on revisit intention using memorable tourism experience as a mediator. A total of 112 visitors were involved as samples taken by convenience sampling. The data collected were processed and analyzed using path analysis with SPSS 28. The results showed that all 4a components were significant to memorable tourism experiences, although accessibility and ancillary were not significant to revisit intention and memorable tourism experience was also proven to be significant to revisit intention. In addition, ancillary is a variable that has the greatest influence on memorable tourist experiences, and memorable tourist experience is also a variable that has the greatest influence in increasing the intention to revisit tourists at the Taman Sari Yogyakarta tourist attraction.